The network model and regional policies for European cohesion and integration - Riccardo Cappellin (Employment and regional development policy: Market efficiency versus policy intervention, 2004)
The paper is articulated in three sections. It first confronts three distinct theoretical approaches, which have been defined as: neo-liberal, corporate and local development model. Then it presents a rather extensive data base of key economic indicators, which allow to appreciate the relevance of these different policy approaches, with specific reference to the case of the South-Italian regions (Mezzogiorno). Third, the paper focuses on the issue of knowledge creation and innovation, as the strategic factor of regional competitiveness and growth in the so called learning economy and it highlights the characteristics of an innovation oriented regional policy. Finally, the paper aims to frame this latter policy in a broader European perspective, aiming to promote the international integration of the various regional innovation systems.
hdl:10419/62287; http://EconPapers.repec.org/RePEc:zbw:arlssd:5
Keywords: 330